THE EFFECT OF DIRECT COMPENSATION TOWARDS EMPLOYEE PERFORMANCE IN FRONT OFFICE DEPARTMENT AT ST. REGIS BALI RESORT - Anak Agung William Vikha Nanda; Nyoman Gde Dewa Rucika; Mahendra Adi Winatha; Hilda Apriani (Unit Bahasa, Politeknik Pariwisata NHI Bandung, 2020)
Analyzing the effect of direct compensation towards employee performance is essential for every business especially hospitality business. This research’s aims are to determine the effect of direct compensation towards employee performance, and know how to improve the employee performance through direct compensation front office department in St. Regis Bali Resort, based on theory of Mangkunegara and Bangun. The data of this research was collected through distributing online questionnaire, conducting interview, and observing the secondary data. In order to validate the data, data triangulation and SPSS are used when testing the data. The data analysis used are simple linear regression test, t-test, and coefficient determinant test. As the result of the research, there is a positive and significant effect of direct compensation on employee performance in Front Office Department at St. Regis Bali Resort. Thus, knowing the effect of direct compensation towards employee performance as well as optimizing the direct compensation provided are recommended to be done in order to maintain and improve employee performance.